2010
DOI: 10.20467/1091-5710.14.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Learning Caring: The Student’s Experience

Abstract: Caring has been identified as essential for baccalaureate nursing education across all programs of study. This study investigated the lived experience of students learning caring in a college of nursing grounded in a caring philosophy. Two major themes were identified from the research data: Innate Knowing of Self as Caring and Caring in the Curriculum. One student shared this thought, “I knew who I was and I knew I could care about people, but I didn’t know how to use caring in nursing. The educational proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Regardless of the environment, our analysis of the outcomes of the considered studies does suggest that using techniques such as role modeling or community engagement does seem to be an effective manner of teaching nursing students how to recognize different world-views and respond with the appropriate provision of caring. [40] Another consistency that we found across most studies was students' reflection on their actions and the situations related to caring. In the research studies that met our review criteria we found that the caring education interventions involved encouraging students to use reflection and discussion to process the experiences they had.…”
Section: Student Outcomesmentioning
confidence: 63%
See 1 more Smart Citation
“…Regardless of the environment, our analysis of the outcomes of the considered studies does suggest that using techniques such as role modeling or community engagement does seem to be an effective manner of teaching nursing students how to recognize different world-views and respond with the appropriate provision of caring. [40] Another consistency that we found across most studies was students' reflection on their actions and the situations related to caring. In the research studies that met our review criteria we found that the caring education interventions involved encouraging students to use reflection and discussion to process the experiences they had.…”
Section: Student Outcomesmentioning
confidence: 63%
“…[25,34,[36][37][38] Similarly, some interventions involved students engaging in role modeling opportunities as nurses and patients and then reflecting on the levels of perceive caring provide and received which was documented to successfully enhance the levels of caring in undergraduate nursing students. [39][40][41] Taking a different approached some successful interventions involved engaging students in service learning experiences which allowed the students to effectively interact with those requiring care. [42,43] The service learning interactions afforded students the opportunity experience caring for others in authentic situations which led them to develop a deeper sense of caring.…”
Section: How Caring Is Taughtmentioning
confidence: 99%
“…Many scholars believe that caring is learned through direct first‐hand experience from faculty; and indirectly through role modelling from faculty and staff (Kosowski , Adamski et al . , Drumm & Chase ). Understanding the impact of caring on nursing education is not only of value to training systems in the United States, but also to systems elsewhere (Lee‐Hsieh et al .…”
Section: Introductionmentioning
confidence: 99%
“…Students need to experience caring first‐hand and at the level of action and interaction to facilitate socialization and internalization of caring attitudes and behaviours (Lee‐Hsieh et al . , Drumm & Chase ). Caring has to be experienced first so one can learn how to care for others (Kosowski , Adamski et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation